2014
DOI: 10.1093/geronb/gbu137
|View full text |Cite
|
Sign up to set email alerts
|

How Dementia Affects Personal Dignity: A Qualitative Study on the Perspective of Individuals With Mild to Moderate Dementia: Table 1.

Abstract: Given the considerable impact the social environment has on the personal dignity of people with mild to moderate dementia, it is important in caregiving not to confine attention to health-related or even any individual aspects alone, but also to take interpersonal aspects into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 53 publications
1
48
1
12
Order By: Relevance
“…Recent qualitative studies have privileged the voices of people living with dementia [24], exploring the impact of dementia upon quality of life [25] and dignity [26]. None have directly considered how people living with dementia in their own homes feel they can best achieve independence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative studies have privileged the voices of people living with dementia [24], exploring the impact of dementia upon quality of life [25] and dignity [26]. None have directly considered how people living with dementia in their own homes feel they can best achieve independence.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature [37,38], there is a discrepancy between caregiver and patient perspectives, and caregivers may have a more negative perspective regarding the function and daily life of patients. According to a qualitative analysis of in-depth interviews with people with dementia [39], a key factor in preserving personal dignity is engagement in meaningful activities within the safe and secure environment of the patient's home. This previous report found that home is "a symbol of the identity the participant had built up over a lifetime".…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative approach A qualitative approach has the potential to offer an in-depth view as well as a description of factors that facilitate or impede the associated social perceptions of older adults (with/without dementia) [79,80]. A growing body of literature has found the method useful in eliciting individual's beliefs, values and attitudes, behavioral practice, meaning and process of ageing and perceptions on dementia [81][82][83][84][85]. This approach can explore the heterogeneous characteristics of older adults where testing a hypothesis might not be a suitable attempt to capture these conceptual phenomena [79,86].…”
Section: Methodological Considerations In Ageing and Dementia Researchmentioning
confidence: 99%